Surprisingness and Occupational Engagement Influence Affective Forecasting in Career-Relevant Contexts - Lu, Di; Jiao, Runkai; Li, Feifei; Lin, Xiaoqing; Yin, Hang (Frontiers in Psychology, 2022)
People tend to misestimate their future emotions. This phenomenon is thought to be associated with information accessibility. However, few studies have demonstrated the impact of context-specific information accessibility on affective forecasting. This research investigated the effects of information accessibility on affective forecasting in career context (i.e., occupational engagement was seen as information accessibility), during which surprise or not surprise context was played simultaneously. We found that affective forecasting appeared stably across emotional responses types. Specifically, there was an underestimation in interest appraisals and an overestimation in satisfaction. These biases were influenced by occupational engagement, which only worked in career interest appraisals. High occupational engagement made people estimate their future emotions more accurately and overcome their forecasting bias. Surprisingness was then manipulated further to explain whether it could impact the effect of occupational engagement on affective forecasting. The emotional responses in both prediction and experience were affected by surprisingness, thus causing no affective forecasting biases. These results suggest the role of occupational engagement in affective forecasting and provide evidence supporting the information accessibility model about the mechanism in affective forecasting.